Pengaruh Tingkat Aksesibilitas Mobil Penumpang Umum Terhadap Perkembangan Ekonomi Masyarakat Di Kabupaten Sikka Provinsi NTT - Alfridus Gado; Ismiyati Ismiyati; Mudjiastuti Handajani (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2021)
The road conditions with potholes, hilly topography, and narrow roads are factors that affect accessibility in the Sikka Regency area. This study aims to examine the level of accessibility of public passenger cars and their effect on the economic development of the community in the research location. This study uses a combined quantitative-qualitative research method with analysis of the level of accessibility and linear regression analysis. The results show that the level of accessibility in Paga District and Bola District is moderate, which means that public passenger car access is not smooth, while the level of accessibility in Magepanda District is very high, which means that access to public passenger cars is very smooth. Then accessibility has a significant effect on the economic development of the community in Paga District and Magepanda District, while accessibility does not have a significant effect on the economic development of the community in Bola District. This condition is caused in addition to the steep topography and damaged road conditions, but also the number of fleets and inadequate conditions that will affect activities to carry out agricultural product sales transactions.